2021
DOI: 10.3390/rs13183735
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Satellite InSAR for Landslide Forecasting: Limitations and Openings

Abstract: The paper explores the potential of the satellite advanced differential synthetic aperture radar interferometry (A-DInSAR) technique for the identification of impending slope failure. The advantages and limitations of satellite InSAR in monitoring pre-failure landslide behaviour are addressed in five different case histories back-analysed using data acquired by different satellite missions: Montescaglioso landslide (2013, Italy), Scillato landslide (2015, Italy), Bingham Canyon Mine landslide (2013, UT, USA), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(19 citation statements)
references
References 73 publications
(93 reference statements)
1
18
0
Order By: Relevance
“…The continuous linear deformation trends and identification of precursory slope movements by InSAR are similar to other published studies (e.g. Dong et al 2017;Handwerger et al 2019;Moretto et al 2021). In particular, the study by Dong et al (2017) on the Xinmo landslide using Sentinel-1 data showed an acceleration of surface displacement, similar to P1 in Fig.…”
Section: Detecting Acceleration Prior To Failuresupporting
confidence: 88%
“…The continuous linear deformation trends and identification of precursory slope movements by InSAR are similar to other published studies (e.g. Dong et al 2017;Handwerger et al 2019;Moretto et al 2021). In particular, the study by Dong et al (2017) on the Xinmo landslide using Sentinel-1 data showed an acceleration of surface displacement, similar to P1 in Fig.…”
Section: Detecting Acceleration Prior To Failuresupporting
confidence: 88%
“…DEM data were utilized to eliminate the flat land phase and topographic effect in order to generate the time series interference phase. The interference phase of the master and slave image [ 40 , 41 , 42 ] was as follows: where is the terrain phase, is the deformation phase, is the atmospheric delay phase, is the flat phase, and is the noise phase. The effective deformation data was extracted using phase unwrapping, and the deformation rate was inversed using singular value decomposition (SVD).…”
Section: Methodsmentioning
confidence: 99%
“…• In recent years, the use of Synthetic Aperture Radar (SAR), particularly interferometry SAR (InSAR), has emerged as a well-established technique in landslide monitoring, identification of precursory signatures for catastrophic slope failures, forecasting and early warning (Carlà et al 2019;Chae et al 2017). InSAR's ability to day-and-night observation, remote area detection, cloud-free and wide-swath datasets makes it a potential and powerful tool for early detection of landslide-critical conditions (Moretto et al 2021). However, there are still limitations and challenges, both technical and operational, which need to be overcome to implement landslide forecasting (Moretto et al 2021).…”
Section: Early Warning Systemsmentioning
confidence: 99%
“…InSAR's ability to day-and-night observation, remote area detection, cloud-free and wide-swath datasets makes it a potential and powerful tool for early detection of landslide-critical conditions (Moretto et al 2021). However, there are still limitations and challenges, both technical and operational, which need to be overcome to implement landslide forecasting (Moretto et al 2021). • The seismic signals also play an important role in monitoring the landslides and help progress towards potential early warning for catastrophic landslides.…”
Section: Early Warning Systemsmentioning
confidence: 99%